2020
DOI: 10.1111/gcb.15164
|View full text |Cite
|
Sign up to set email alerts
|

Structure and parameter uncertainty in centennial projections of forest community structure and carbon cycling

Abstract: Secondary forest regrowth shapes community succession and biogeochemistry for decades, including in the Upper Great Lakes region. Vegetation models encapsulate our understanding of forest function, and whether models can reproduce multidecadal succession patterns is an indication of our ability to predict forest responses to future change. We test the ability of a vegetation model to simulate C cycling and community composition during 100 years of forest regrowth following standreplacing disturbance, asking (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 134 publications
(163 reference statements)
1
34
0
1
Order By: Relevance
“…The relevant parameters are again further described in Table 1. The complete description of the radiative transfer model of ED2 can be found in Appendix A, in Longo et al (2019a), or in Shiklomanov et al (2020).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The relevant parameters are again further described in Table 1. The complete description of the radiative transfer model of ED2 can be found in Appendix A, in Longo et al (2019a), or in Shiklomanov et al (2020).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Model structure complexity varies among TBMs and also depends on the user configuration choices: different formulations of the same process can co-exist within a TBM. This complexity results from the necessary compromise between an accurate representation of the reality on the one hand and the computational demand and observational requirements on the other (Shiklomanov et al 2020). Model intercomparison studies have demonstrated that discrepancies in the representation of key processes such as forest structure (Fisher et al 2018) or photosynthesis (Rogers et al 2017) lead to significant uncertainties in the projections of critical variables such as the overall land carbon sequestration capacity (Friedlingstein et al 2014;Lovenduski and Bonan 2017;Friedlingstein et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous sensitivity analyses have underlined the critical importance of parameter uncertainty for the projections of ecosystem demography and productivity (Dietze et al 2014;Massoud et al 2019;Raczka et al 2018;Wramneby et al 2008). In a recent comparative study, parameter uncertainty was even shown to drive the overall model uncertainty (Shiklomanov et al 2020). Among model parameters, allometric coefficients scale the shape and mass of the plants or of its components with their size (Chave et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1). Data from the field experiment also inform a series of modeling experiments; specifically, data included in this package are used to initialize, calibrate, and validate dynamic vegetation model simulations of forest function and its responses to disturbance (e.g., Shiklomanov et al, 2021).…”
Section: The Forte Projectmentioning
confidence: 99%
“…Disturbance alters multiple carbon (C) cycling processes and, as a result, may affect forest C uptake and storage (Williams et al, 2016). The magnitude, timing, and duration of changes in the C cycle following disturbance vary among forests (Amiro et al, 2010;Luo and Weng, 2011;Coomes et al, 2012;Hicke et al, 2012;Gough et al, 2013;Peters et al, 2013;Vanderwel et al, 2013;Flower and Gonzalez-Meler, 2015;Gu et al, 2019). These responses may differ as a function of disturbance severity, type, and frequency along with the physical, structural, and biological properties of the affected ecosystem (Amiro et al, 2010;Williams et al, 2012;Scheuermann et al, 2018;Rebane et al, 2019;Atkins et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%